Intubation, tracheostomy, and decannulation in patients with Guillain–Barré–syndrome—does dysphagia matter?. Issue 2 (18th December 2018) - Schröder, Jens Burchard; Marian, Thomas; Muhle, Paul; Claus, Inga; Thomas, Christian; Ruck, Tobias; Wiendl, Heinz; Warnecke, Tobias; Suntrup‐Krueger, Sonja; Meuth, Sven; Dziewas, Rainer
ABSTRACT: Introduction : Although patients with Guillain–Barré syndrome frequently require orotracheal intubation and tracheostomy, the incidence and relevance of neurogenic dysphagia prior to intubation and risk factors for prolonged requirement for a tracheal cannula have not yet been identified. Methods : Retrospective analysis of the medical records of 88 patients was performed. Clinical characteristics were compared between intubated and nonintubated patients and between immediately decannulated and not immediately decannulated patients. Results : Thirty‐five (39.7%) patients required tracheostomy. Neuromuscular weakness and related respiratory insufficiency were the main reasons for intubation. In the subgroup of tracheotomized patients, immediate decannulation after completed respiratory weaning was possible in 14 (40%) patients. The severity of dysphagia, in particular pharyngolaryngeal hypesthesia, was related to the length of cannulation. Discussion : Respiratory muscle weakness is the main reason for intubation, whereas neurogenic dysphagia is the main risk factor for persisting cannulation. Dysphagia after weaning is most frequently characterized by severe laryngeal sensory deficit. Muscle Nerve 59 :194–200, 2019